DETERMINANT DETECTION OF TRANSFER PRICING DECISIONS - Sulistyawati, Ardiani Ika; Santoso, Aprih; Rokhawati, Liana (ACCOUNTABILITY, 2020)
This study aims to verify and analyze the effect of tax minimization, tunneling incentive and bonus mechanisms against the decision of transfer pricing. The population in this study are all companies registered in the Indonesia Stock Exchange unless the moving company financial sector during the period 2015-2017. While the sampling process using a purposive sampling method and the sample obtained as many as 132 companies. Tax minimization proxied using ETR (effective tax rate), tunneling incentive proxied using the percentage of foreign ownership above 20%, and a mechanism that is measured by the percentage of net profit in year t to the year t-1.This research is a quantitative research and data used in this research is secondary data obtained from the company's annual report in 2015-2017 sourced from www.idx.co.id. This study analyzes the data by using logistic regression with SPSS 23.0. The results of this study indicate that tax minimization variables influence the decision of transfer pricing. This study also shows that the tunneling incentive effect on transfer pricing decisions while the variable bonus mechanism does not affect the decision of transfer pricing.